2012
DOI: 10.1159/000331598
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Suicidal Ideation in College Students

Abstract: Background/Aims: Suicide is one of the leading causes of death in college students and is often associated with depression. The aim of this study was to assess the rates of suicidal ideation (SI) on college campuses and to identify its correlates. Methods: On-campus depression screening sessions were conducted at 3 universities (n = 898; 55% female; mean age 20.07 ± 1.85 years). Participants completed the Beck Depression Inventory (BDI; mean ± SD of total score = 6.27 ± 6.31) and other measures. Eighty-four st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 31 publications
3
58
0
3
Order By: Relevance
“…The results of the current article are based on a subset of data drawn from a larger study (see Farabaugh et al, 2012, for a description of the parent study). Briefly, the study included undergraduate college students who gave informed consent to participate in a mental health screening at their university.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the current article are based on a subset of data drawn from a larger study (see Farabaugh et al, 2012, for a description of the parent study). Briefly, the study included undergraduate college students who gave informed consent to participate in a mental health screening at their university.…”
Section: Methodsmentioning
confidence: 99%
“…Given that many students with suicidal ideation do not seek treatment, it is critical to implement screening strategies to identify them and engage them in treatment [14, 15]. Among the major risk factors for suicide in this age group are depression [16], hopelessness [17, 18], and substance use [19, 20]. …”
Section: Prevalence Of Mental Health Disordersmentioning
confidence: 99%
“…In the spring 2012 American College Health Association National College Health Assessment of students from 141 self-selecting postsecondary education institutions, over one-fifth of undergraduate students reported a current or previous diagnosis with depression [1]. Studies have identified depression among college students as a risk factor for poor academic performance [2,3], problem drinking [4], suicidal thoughts [5,6], frequent illness [7], and college dropout [8]. …”
Section: Introductionmentioning
confidence: 99%